Cycling and Health in an Ageing Society. Report on AENEAS Training Workshop 9 and 10 June 2010 City of Odense. - Fiedler, Matthias; Bemmelen, Maarten van (My University, 2010)
Attaining Energy-Efficient Mobility in an Ageing Society (AENEAS) is a project which aims to apply soft measures (e.g. training, individualised travel marketing, awareness raising and events) in five European cities to encourage and enable older people to use alternatives to the private car.
Keywords: Individualverkehr; Fahrradverkehr; Mobilität; Gesundheit; Mobilitätsmanagement; Demographischer Wandel; Senior; Mobilitätsverhalten; Fahrradnutzung; Gesundheitsförderung